The great cat caper - Snelling, Lauraine (Snelling, Lauraine. S. A. V. E. squad., 2012)
Join the S.A.V.E. Squad -- Sunny, Aneta, Vee, and Esther -- as the four sixth-grade girls, with nothing in common but their differences, come together through a service learning project to rescue dumpster cats.